Fixed point theorems for generalized Lipschitzian semigroups in Banach spaces. (1st March 1999) - Thakur, Balwant Singh; Jung, Jong Soo
Abstract : Fixed point theorems for generalized Lipschitzian semigroups are proved inp -uniformly convex Banach spaces and in uniformly convex Banach spaces. As applications, its corollaries are given in a Hilbert space, inL p spaces, in Hardy spaceH p, and in Sobolev spacesH k, p, for1 < p < ∞ andk ≥ 0 .